2017
DOI: 10.1155/2017/3190301
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Findings in Patients with Medication-Related Osteonecrosis of the Jaw

Abstract: A retrospective study was conducted of the records and panoramic radiographs of 35 patients treated with bisphosphonates (BP) and diagnosed with MRONJ. Panoramic radiography was used for evaluation, by two examiners, the following findings were subject of search: osteolysis (OT), cortical bone erosion (EC), bone sclerosis focal (FS) and diffuse (DS), bone sequestration (BS), thickening of lamina dura (TD), prominence of the inferior alveolar nerve canal (IAN), persisting alveolar sockets (SK), and the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
0
20
0
18
Order By: Relevance
“…2 Despite histopathological and clinical similarities, the above-mentioned pathologies also exhibit very similar image characteristics. 7,8 Authors have presented a detailed image description comparing BRONJ and ORNJ from dental panoramic radiographs and computed tomography and have pointed out a number of similarities between the two pathologies, such as osteolysis, osteosclerosis, sequestration, and dissemination of soft tissue inflammation, emphasizing only two main differences between them, namely predominant osteolysis in ORNJ and osteosclerosis in MRONJ cases. 7 There are few pathological studies comparing OMJ, MRONJ, and ORNJ in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite histopathological and clinical similarities, the above-mentioned pathologies also exhibit very similar image characteristics. 7,8 Authors have presented a detailed image description comparing BRONJ and ORNJ from dental panoramic radiographs and computed tomography and have pointed out a number of similarities between the two pathologies, such as osteolysis, osteosclerosis, sequestration, and dissemination of soft tissue inflammation, emphasizing only two main differences between them, namely predominant osteolysis in ORNJ and osteosclerosis in MRONJ cases. 7 There are few pathological studies comparing OMJ, MRONJ, and ORNJ in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Osteonekroz, radyografide kemik sklerozu, lamina duranın kalınlaşması, komşu kortikal kemiğin erozyonu, periost reaksiyonu, spinal trabeküler kemiğin bozulması, çekim soketinde gecikmiş remodeling, mandibular kanalın belirginleşmesi, sekestrasyon ve patolojik kırık şeklinde kendini gösterir. 11,33 Yapılan çalışmalarda en sık karşılaşılan radyografik bulgular kemik sklerozu ve osteoliz olarak belirtilmiştir. 34,35 Ancak osteonekrozun erken evresinde anlamlı kemik tutulumu ve demineralizasyon olmadan panoramik radyografiler bulgu vermez.…”
Section: Mronj'un Radyografik Bulgularıunclassified
“…9 MRONJ'un bazı radyografik görüntüleri de osteomiyelit, osteoradyonekroz ve kemik metastazları gibi diğer kemik hastalıklarıyla benzerlik gösterebilir, bu nedenle ayrıntılı tıbbi ve fizik muayene, doğru tanı ve tedavi planlamasında önem arz etmektedir. 33…”
Section: Ayırıcı Tanılarunclassified
“…All of them recruited patients that had been treated with antiresorptive bone therapy for either oncological or non-oncological reasons. The studies were observational studies either descriptive 3,[5][6][7]9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] or analytical cross-sectional, 10,[35][36][37][38][39] analytical cohort, 40 or analytical case-control. 41 Only one included study was an analytical cohort, 40 as well as, only one analytical case-control 41 study was found.…”
Section: Study Characteristicsmentioning
confidence: 99%